6-Cyanonaphthalen-2-yl 4-hexylbenzoate - Rahman, Md. Lutfor; Srinivasa, H. T.; Mohd. Yusoff, Mashitah; Huey, Chong Kwong; Ching, Kheng Quah (International Union of Crystallography, 2014)
In the title compound, C24H23NO2, a whole molecule is disordered over two sets of sites with occupancies in a ratio of 0.692 (6):0.308 (6). In the major disorder component, the naphthalene ring system forms a dihedral angle of 68.6 (5)° with the benzene ring. The corresponding angle in the minor component is 81.6 (10)°. In the crystal, molecules are linked into chains propagating along the b-axis direction via weak C—H...O hydrogen bonds. The crystal packing is further consolidated by weak C—H...n interactions.